Privacy concerns and online purchasing behaviour: towards an integrated model - Fortes, N. (2016)
This study aims to analyze how privacy concerns about the Internet have an impact on the consumer's intention to make online purchases. A research model was developed establishing that this impact takes place via the connection of privacy concerns with the theories of trust and risk, the theory of planned behaviour and the technology acceptance model. The empirical study was based on an online survey that collected data from 900 individuals. The results confirmed the acceptance of all proposed hypotheses and the overall validation of the research model. Implications and further research suggestions are presented.